KESESUAIAN ANTARA KEPUASAN WISATAWAN PEJALAN KAKI DAN TINGKAT WALKABILITY PADA KAWASAN WISATA TAMANSARI DAN PASAR NGASEM YOGYAKARTA (Jurnal Arsitektur ARCADE, 2026)
Cultural heritage tourism areas rely on pedestrian movement because walking is an integral part of the tourism experience. Previous studies generally evaluated walkability based on objective physical conditions or examined tourist satisfaction separately, resulting in limited understanding of the extent to which walkability influences tourist satisfaction. This study aims to analyze the correlation between walkability and tourist satisfaction along the pedestrian path leading to the Tamansari Cultural Heritage Area and Ngasem Market, Yogyakarta. A quantitative approach with an evaluative and comparative design was used. Walkability was assessed through field observations, while tourist satisfaction was measured using a questionnaire distributed to visitors. Data were analyzed using assessment and analysis techniques to compare objective walkability with subjective tourist perceptions. The results show that the correlation varies across variables. The highest correlation was found for visual appeal, particularly the presence of cultural heritage elements, as a determining factor in walkability satisfaction. The lowest correlation was found for perceptions of barrier-free pedestrian conditions and the visual quality of buildings and surrounding views. These findings suggest that pedestrian tourist satisfaction is influenced not only by the physical quality of pedestrian facilities but also by the overall walking experience, highlighting the importance of integrating physical and perceived walkability assessments in cultural heritage tourism areas.